Revisión: Producción de Biodiesel a partir de algas - Rodríguez Robles, Carlos Alejandro (2017)
The aim of this review to provide enough information to industrial producer of biodiesel about the qualities and characteristics of algae, so that it can carry out a proper selection and use of them. Algae are acquiring an important role, from being just simple aquatic plants to be considered as excellent feedstocks for the production of biodiesel, because the product made of them has properties as their non-toxicity, biodegradability, renewability, etc. Algae for biodiesel production are exploited under specific conditions developed technologies, which must be considered by the producers because the results are modified according to the species to be used, type of cultivation and harvesting, extraction method and application area. The available information suggests that the scope of algae as recent renewable source is directed towards: (a) a more profitable farming, (b) satisfaction in the global demand for transport fuels, (c) better control environmental pollution, (d) human nutrition by providing lots of nutritional supplements, (e) animal feed and (f) the pharmaceutical industry.